2008
DOI: 10.1007/s00792-008-0192-4
|View full text |Cite
|
Sign up to set email alerts
|

Amino acid contacts in proteins adapted to different temperatures: hydrophobic interactions and surface charges play a key role

Abstract: Thermophiles, mesophiles, and psychrophiles have different amino acid frequencies in their proteins, probably because of the way the species adapt to very different temperatures in their environment. In this paper, we analyse how contacts between sidechains vary between homologous proteins from species that are adapted to different temperatures, but displaying relatively high sequence similarity. We investigate whether specific contacts between amino acids sidechains is a key factor in thermostabilisation in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
45
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 43 publications
4
45
0
Order By: Relevance
“…Another study that analyzed the sequence of nearly 400 cold-adapted proteins, also reported similar differences at the protein surface, consistent with alterations in amino acid contacts with the solvent [31]. Changes at the surface resulted in greater entropic effects rather than specific effects like diminished numbers of salt bridges.…”
Section: Discussionmentioning
confidence: 64%
“…Another study that analyzed the sequence of nearly 400 cold-adapted proteins, also reported similar differences at the protein surface, consistent with alterations in amino acid contacts with the solvent [31]. Changes at the surface resulted in greater entropic effects rather than specific effects like diminished numbers of salt bridges.…”
Section: Discussionmentioning
confidence: 64%
“…Higher proline percentage for thermostable protein shows its pronounced role in enhancing thermostability as it is more rigid than other amino acids and reduces the entropy of the main chain polypeptide decreasing the chance of unfolding at elevated temperatures [46]. The results in the present study have clearly showed that proline is higher in both ends of temperature when compared to moderate inhabitant.…”
Section: Discussionsupporting
confidence: 51%
“…However, a very high abundance of a single species or members of the phylum will influence clustering of samples based on phylum level abundances. Previous studies identified differences in the amino acid composition between mesophiles and thermophiles [35], [36], which originated at differences in genomic GC content as well as changes of relative frequencies of certain amino acids that affected the thermal stability of the protein [37], [38]. The most variability of the amino acid profiles of the thermophiles was well justified by the genomic GC content, temperature having only little significant effect [39].…”
Section: Discussionmentioning
confidence: 99%